Memantine augmentation for refractory obsessive–compulsive disorder - Pasquini, Massimo; Biondi, Massimo (Progress in neuro-psychopharmacology & biological psychiatry, 2006)
Glutamatergic hyperactivity hypothesis in obsessive–compulsive disorder (OCD) has been proposed but not tested. Memantine is an uncompetitive N-methyl- d-aspartate (NMDA) receptor antagonist. We report two cases of refractory obsessive–compulsive disorder treated with an augmentation of memantine at 15 mg/day. The first case did not benefit from such treatment, while the second showed immediate and substantial improvement. Contrasting results, reflecting different subtypes of OCD, are discussed. We hypothesized that in certain OCD subtypes an agent that enhances memory for actions may promote a reduction in orbitofrontal activation.